Practice of giving exclusive breastfeeding among the babies of working mothers and house wife mothers- a comparative study - Hassan, Mahmuda; Yasmeen, BH Nazma; Ahmed, Taslim Uddin; Begum, Marium; Rob, AWS; Ahmed, Ashraf Uddin; Rahman, Hamidur (Northern International Medical College Journal, 2015)
Objectives : There is gradual reduction of exclusive breast feeding practice as age advances from birth to 6 months. The aim of the study was to see the status of exclusive breast feeding up to 6 month of age, among the babies of working mothers and housewife mothers and also to see different contributing factors among the working mothers for the initiation of breast milk substitute within this period. Material and Methods : This is a descriptive type of study conducted in Ad- Din Hospital at OPD from 1st January 2008 to 31st December 2009.Total 400 babies were selected, among them 200 were the babies of the working mothers, considered as cases and 200 were the babies the of housewives considered as control. Sampling was done purposively. Then babies of working mothers were divided in to 2 groups according to their age- (Group-I babies of 3 months±15 days and Group-II 6 months±15 days). Also babies of the housewife mothers were also divided in to 2 groups (Group-I IIbabies of 3 months±15 days and Group-IV 6 months±15 days). Each group includes 100 babies. Mothers or caregivers of their babies were interviewed only once for the study with a set questionnaire. Results : Seventy eight percent (78%) working mothers were continued exclusive breast feeding up to 3 months±15 days but at the age of 6 months±15 days only 21% babies were continued exclusive breast feeding . On the other hand at the age of 3 months ±15days 66% and at 6 months ±15days of age 45% babies of housewife mothers were continued exclusive breast feeding. Highly significant reduction of exclusive breastfeeding among babies of working mothers (p value< 0.001) and also that of the housewife mothers (p value<0.05). Significant number of mothers (more than 80%)of both the groups had no or inadequate knowledge about expression and preservation of breast milk (p value <0.001 ). Maternity leave was less than 6 months, 4 months in government organization (GO) and even 45 days for in some non government organization (NGO) were observed. Conclusion : Exclusive breast feeding up to 6 months of age less among the babies of working mothers even with a good start. Lack of knowledge about expressed breast milk, policy adopted by the employers and maternity leave less than 6 months are the main contributing factors for reduction of exclusive feeding. Northern International Medical College Journal Vol.5(2) 2014: 339-341